2017
DOI: 10.1163/15685411-00003040
|View full text |Cite
|
Sign up to set email alerts
|

Ditylenchus laurae sp. n. (Tylenchida: Anguinidae) from Poland – a new species of the D. dipsaci complex associated with a water plant, Potamogeton perfoliatus L.

Abstract: The genus Ditylenchus consists of more than 60 species, some of which are plant parasites. In this paper we report on Ditylenchus laurae sp. n. from Poland, a new species associated with the aquatic plant, Potamogeton perfoliatus L. Ditylenchus laurae sp. n. is characterised by a long and slender body with L = 1881 (1523-2095) μm and 1875 (1690-2089) μm, a = 88.8 (72.5-102.5) and 89.7 (71.9-97.9), stylet length = 10.8 (9.6-12.1) μm and 8.3 (7.7-9.0) μm, tail length = 117.2 (103.5-126.7) μm and 102.4 (98.3-113.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Recent phylogenetic studies do not concur on the paraphyletic status and presence of different lineages in Ditylenchus [10,11,60]. In our study, we noted that phylogenetic inference is effective for separating species, but with limited sequence-based information, these inferences are inconclusive in assigning species groups (D. dipsaci or D. triformis) or predicting the relationship among these species.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Recent phylogenetic studies do not concur on the paraphyletic status and presence of different lineages in Ditylenchus [10,11,60]. In our study, we noted that phylogenetic inference is effective for separating species, but with limited sequence-based information, these inferences are inconclusive in assigning species groups (D. dipsaci or D. triformis) or predicting the relationship among these species.…”
Section: Discussioncontrasting
confidence: 61%
“…Newly obtained sequences and other known Ditylenchus species' DNA sequences present in GenBank were used for phylogenetic analysis. The selection of outgroup taxa for each dataset was based on published studies [6,10,11,60]. Multiple nucleotide sequence alignments for the different genes were performed using the heuristics progressive method FFT-NS-2 algorithm of MAFFT v7.450 [69].…”
Section: Phylogenetic Studiesmentioning
confidence: 99%
“…Nematodes from the genus Ditylenchus Filipjev, 1936, are found in soil, in the root zone of arable and wild--growing plants, and occasionally in the tissues of underground or aboveground parts (Brzeski 1998). This genus includes approximately 80-90 accepted species (Brzeski 1991;Qiao et al 2016) of which more than 20 have been reported in Poland (Brzeski 1998;Wi niszewska 2008;Jeszke et al 2014;Skwiercz et al 2017). The majority of Ditylenchus are associated with terrestrial plants and only two representatives of this genus were found to be parasites of aquatic ones (Skwiercz et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This genus includes approximately 80-90 accepted species (Brzeski 1991;Qiao et al 2016) of which more than 20 have been reported in Poland (Brzeski 1998;Wi niszewska 2008;Jeszke et al 2014;Skwiercz et al 2017). The majority of Ditylenchus are associated with terrestrial plants and only two representatives of this genus were found to be parasites of aquatic ones (Skwiercz et al 2017). The researchers' interest in the genus Ditylenchus is primarily due to the role which some of the representative species play in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, despite the wide distribution of R. goodeyi across Europe, its molecular information in public databases is scarce, with only one partial sequence of both the 18S (AY284609) and the 28S of ribosomal DNA (rDNA; DQ328756) available in Gen-Bank before this study. Conversely, more and more molecular data including mitochondrial gene fragments are gradually being generated for Rotylenchus and other plant-parasitic nematode (PPN) species of various degrees of economic importance (Cantalapiedra-Navarrete et al 2013;Etongwe et al 2020;Guti errez-Guti errez et al 2012;Holguin et al 2015;Kumari and Subbotin 2012;Rybarczyk-Mydłowska et al 2019;S anchez-Monge et al 2017;Singh et al 2021b;Skwiercz et al 2017;Subbotin et al 2017; Van den Berg et al 2017;van de Vossenberg et al 2013;Vovlas et al 2015), and an increasing affordability of high-throughput sequencing (i.e., next-generation sequencing) also provides new possibilities to unravel more complete gene sequence information for important PPN species (Besnard et al 2014;Ma et al 2020;Zheng et al 2016). In particular, the mitochondrial genome is known as a useful source of molecular markers for DNA barcoding, phylogenetic relationships, and population genetic and phylogeographical studies (Humphreys-Pereira et al 2020).…”
mentioning
confidence: 99%